STRATEGI PEMBENTUKAN KEPERCAYAAN DIRI REMAJA PASCA MENGHADAPI BULLYING DI YOGYAKARTA - Septiani, Icha; Setiyani S, Ratna Yunita (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT Bullying is a serious problem that impacts adolescents' self-confidence. This study aims to analyze strategies for building self-confidence in adolescents after experiencing bullying in Yogyakarta. This qualitative research with a case study approach involved one main subject (female, 20 years old) and two significant others (subject's mother, 53 years old; close friend, 21 years old) selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then analyzed using thematic analysis based on Lauster's four aspects of self-confidence: believing in one's abilities, acting independently in decision-making, having a positive self-concept, and being brave in expressing opinions. The results show that the subject successfully rebuilt self-confidence through internal strategies such as positive affirmations, self-reflection, and self-concept reinforcement, as well as external strategies such as social support from family and friends, and the independent decision to change schools. These findings indicate the effectiveness of combining positive affirmations and social support in recovering self-confidence among adolescent bullying victims, with recommendations for implementing group counseling programs and positive affirmation interventions in schools to support psychological recovery. ABSTRAK Bullying adalah masalah serius yang berdampak pada kepercayaan diri remaja. Penelitian ini bertujuan untuk menganalisis strategi membangun kepercayaan diri pada remaja setelah mengalami bullying di Yogyakarta. Penelitian kualitatif ini dengan pendekatan studi kasus melibatkan satu subjek utama (perempuan, 20 tahun) dan dua orang signifikan lainnya (ibu subjek, 53 tahun; teman dekat, 21 tahun) yang dipilih melalui purposive sampling. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi, kemudian dianalisis menggunakan analisis tematik berdasarkan empat aspek kepercayaan diri Lauster: percaya pada kemampuan sendiri, bertindak mandiri dalam pengambilan keputusan, memiliki konsep diri positif, dan berani mengungkapkan pendapat. Hasil penelitian menunjukkan bahwa subjek berhasil membangun kembali kepercayaan diri melalui strategi internal seperti afirmasi positif, refleksi diri, dan penguatan konsep diri serta strategi eksternal seperti dukungan sosial dari keluarga dan teman, serta keputusan mandiri untuk pindah sekolah. Temuan ini menunjukkan efektifitas kombinasi afirmasi positif dan dukungan sosial dalam pemulihan kepercayaan korban bullying remaja, dengan rekomendasi penerapan program konseling kelompok dan intervensi afirmasi positif di sekolah untuk mendukung pemulihan psikologis.